Examining Workplace Ostracism Experiences in Academia: Understanding How Differences in the Faculty Ranks Influence Inclusive Climates on Campus - Zimmerman, Carla A.; Carter-Sowell, Adrienne R.; Xu, Xiaohong (Frontiers in Psychology, 2016)
Research on the retention of women in academia has focused on challenges, including a “chilly climate,” devaluation, and incivility. The unique consequences of workplace ostracism – being ignored and excluded by others in an organizational setting – require focus on this experience as another interpersonal challenge for women in academia. The purpose of this study is to examine differences in the faculty experiences and outcomes of workplace ostracism, and to determine if these experiences are affected significantly by the gender composition of an employee’s specific department. Participants were recruited at two time points to complete campus climate surveys that were distributed to faculty at a large, public, research university. We examined the number of reported ostracism experiences (Study 1) and perceived information sharing (Study 2) among male and female university faculty. The findings indicated that female faculty members perceived more workplace ostracism than male faculty members. Analyses of department gender ratios suggested that the proportion of women in the department did not reduce the amount of workplace ostracism experienced by women. No gender differences were found in perceived information sharing. However, we found that Faculty of Color, both men and women, reported more frequent information exclusion than White faculty. These results have important implications for theoretical and practical understandings of workplace demography and suggest that it is necessary to look at subtle, ambiguous forms of discrimination in order to increase retention of faculty from underrepresented groups in academia.